THE EFFECT OF KOH AND CACO3 SOLUTION CONCENTRATION ON THE QUALITY OF ALKALI TREATED COTTONII CHIPS (ATCC) PRODUCED - Sitti Rahmaniar A; Ratnawaty Fadillah; Andi Sukainah (SUJANA: Education and Learning Review, 2024)
The alkali treatment process typically employs KOH (potassium hydroxide) and CaCO3 (calcium carbonate) to modify Cottonii's cellular structure, facilitating carrageenan extraction and enhancing the final product's quality. The concentration of these solutions significantly impacts the quality of Alkali Treated Cottonii Chips (ATCC). This research aims to determine the effect of KOH and CaCO3 concentrations in the soaking and bleaching process on the quality of Alkali Treated Cottoni Chips (ATCC) produced. The ATCC processing was conducted by adding the concentration of KOH and CaCO3 solution in each treatment. Observations made in this research are water content and pH while for the analysis of the test is gel strength and carrageenan. This research is an experimental study using a Completely Randomized Design (CRD) with a factorial pattern consisting of 2 factors. The results of this research indicate the effect of the concentration of KOH and CaCO3 solutions on the processing of Alkali Treated Cottoni Chips (ATCC) is significantly influential on the quality of ATCC where KOH and CaCO3 contribute to the determination of the analysis of the physical and chemical properties of ATCC both from the ability of KOH to inhibit the rate of water content, pH, and the ability of KOH and CaCO3 in gel formation. The maximum standard of water content of ATCC is 12% in this research, the lowest water content is A3B3 with a value of 9.74%, the highest is A1B1 with a value of 11.72%, for the pH of ATCC, the value ranges between pH 8-11, the pH of A1B1 treatment with the lowest value of 8.66 and the highest is A3B3 with a value of 9.22, while for the highest gel strength is A3B3 treatment with a value of 150.70g and for carrageenan, the highest value is obtained in A2B2 treatment with a value of 65.98%.